Comprehensive study of prognostic risk factors of patients underwent pneumonectomy - Gu, Chang (J Cancer, 2017)
Introduction: To investigate postoperative complications and the prognostic risk factors of patients underwent pneumonectomy. Methods: Four hundred and six patients underwent pneumonectomy were subjected to the study. All the clinicopathologic data including age, gender, smoking history, surgical treatment, postoperative complications, tumor staging and the follow-up information were investigated. Results: The 30-day and 90-day mortality rates were 3.2% and 6.2%, respectively. Postoperative complications developed in 149 patients (36.7%), mainly included arrhythmia, transfusion, pulmonary infection, bronchopleural fistula and acute respiratory distress syndrome. During the follow-up, 189 patients experienced a relapse, consisting of 51 patients with local recurrence and 138 with distant recurrence. The median survival time was 24.4 months and the overall 1-year, 3-year and 5-year survival rates were 82.7%, 50.9% and 32.5%, respectively. Moreover, the overall 1-year, 3-year, 5-year survival rates for patients with non-small cell lung cancer (NSCLC) were 84.1%, 52.1% and 32.5%, respectively and patients with small cell lung cancer (SCLC) were 56.1%, 38.5% and 28.8%, respectively. Among NSCLCs, adenocarcinomas had a worse prognosis than squamous carcinomas. Compared to right pneumonectomy, patients with left pneumonectomy had a better prognosis. Multivariable analysis revealed ICU stay, disease stage, nodal stage and adjuvant chemotherapy were all significant predictors of overall survival (OS). Conclusions: Pneumonectomy is still a valuable and effective treatment option for patients with advanced lung cancer. Surgeons should be more cautious when patients had higher disease stage, adenocarcinoma and right-side lung cancer. Neoadjuvant chemotherapy did not affect the prognosis. Pneumonectomy could also achieve acceptable survival outcomes in well-selected SCLC patients.